Perbaikan Sistem Distribusi Dan Transportasi Dengan Menggunakan Distribution Requirement Planning (DRP) Dan Algoritma Djikstra (Studi Kasus : Depot Pertamina Tasikmalaya) - Sumiharni Batubara; Rahmi Maulidya; Irma Kusumaningrum (JURNAL TEKNIK INDUSTRI, 2011)
The competition in petroleum industry to meet customer requirements is very tight. Companies that are able to survive are a company that can meet consumer demand in a timely manner. Companies must pay attention to the smoothness of its distribution system so as to meet consumer demand for continuous and timely. The problems frequently encountered by the Petroleum Industry are a delay in delivery of fuel from depots to filling stations are located in the region such coverage Depot. This is caused by a number of previously unknown oil demands, the limited number of tank cars for fuel and lack of accuracy, adequacy determination of delivery routes fuel from depots to retail outlets. This paper is intended to help the Oil Industry to determine the fuel distribution system and the determination of delivery routes with the aim of minimizing shipping costs and delivery schedules to determine fuel from depots to retail outlets. The method used in this study is the Distribution Requirements Planning (DRP) to determine how the delivery of fuel from depots to retail outlets each with respect to the amount of the daily requirement of each pump.This research begins with forecasting demand for fuel at 81 gas stations for several future periods. Under the DRP method of forecasting at each gas station for one week ahead will be a need for fuel to be supplied by the Depot Tasikmalaya. So that the Depot can estimate the amount of fuel that must be sent to each retail outlets in the coming period. Furthermore Djikstra algorithm used to determine fuel delivery routes from depots to retail outlets. The selected route is a route with a shorter distance and minimum shipping costs. After that car assignment scheduling done by using rule-based scheduling longest travel time (Longest Processing Time), to obtain the finish time of fuel delivery is almost the same on every car is assigned.Use of the DRP method, assignment and scheduling and Djikstra algorithm, tank car is useful because it can estimate the needs of Tasikmalaya Depot gas station in the coming period so that the fuel supply depot in accordance with the requirements both in terms of quantity and time, can determine the route of delivery of fuel depots to gas stations with the shipping costs more low-cost, timely delivery time and workload tank car that is almost the same.